Impact of social media marketing on brand loyalty in Saudi Arabia - Tawfeeq M. Alanazi (International Journal of Data and Network Science, 2023)
The aim of the study is to explore the impact of Social Media Marketing on Brand Loyalty. It focused on customers of small and medium enterprises (SMEs) specializing in the fashion products retail in Saudi Arabia. An online instrument was created through Google Forms and published on social media of SMEs that trade in fashion. In total, (1692) responses were received. Structural equation modeling (SEM) was used to test hypotheses. The results of the research showed that all dimensions of social media marketing had a positive impact on brand loyalty. The highest impact was for social media word of mouth. The study recommends the issuance of more legal legislation to protect user privacy and prevent its penetration, in addition to enacting laws that punish bad use of networks, which increases customers' trust in these sites and motivates them to carry out many marketing campaigns.